Is microcredit reaching the poorest and contributing for the reduction of poverty? - Dias, Liliana Mota (2019)
The purpose of this essay is to understand why Microcredit Institutions, also known as MFIs, spend billions of dollars trying to end poverty by making small loans to impoverished entrepreneurs. MFIs argue that microcredit mitigates market failures, spurs micro-enterprise growth, and boosts borrowers well-being, consequently leading to a massive wave of theoretical speculations, often drawing upon the latest theoretical advances in economics and finance. This essay draws on the existing literature to synthesize the available evidence in a way that allows a comprehensive knowledge of some basic empirical facts. Overall, the results suggest that the expansion of the microcredit industry and high loan repayment ratios is raising questions about the real impact on the client entrepreneurs. The spread of consumer microcredit and uncontrolled growth of microfinance led to over-lending without adequate check and balances. As a result, borrowers cannot repay their loans, so they end up using the new loans to repay the old ones leading to over-indebtedness and associated stress and critique of microcredit.